2017
DOI: 10.3928/01913913-20170309-01
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Oblique Overaction: Anterior Transposition Versus Myectomy

Abstract: Both the inferior oblique myectomy and anterior transposition procedures are effective in reducing IOOA with similar satisfactory results. DVD and hypertropia were also corrected similarly by these two surgical procedures. [J Pediatr Ophthalmol Strabismus. 2017;54(4):232-237.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…study, the preoperative mean IOOA in the myectomy group was higher than the classic recession group. In another study, their results showed that satisfactory improvement in IOOA to a 0 or +1 grade was observed in 26 eyes of the myectomy group (61.9%) and 27 eyes of the classic recession group (67.5%) 12 . Our success in the myectomy group was higher than Rajavi et al.…”
Section: Discussionmentioning
confidence: 45%
“…study, the preoperative mean IOOA in the myectomy group was higher than the classic recession group. In another study, their results showed that satisfactory improvement in IOOA to a 0 or +1 grade was observed in 26 eyes of the myectomy group (61.9%) and 27 eyes of the classic recession group (67.5%) 12 . Our success in the myectomy group was higher than Rajavi et al.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, Stein et al 13 reported an average of 2.8 prism dioptre reduction with the myectomy procedure, as opposed to a 4.0 prism dioptre reduction with the use of anterior transposition six weeks post-operatively. Lastly, Rajavi et al 18 reported no significant difference in hypertropia between the two groups.…”
Section: Primary Outcome Residual Inferior Oblique Functionmentioning
confidence: 93%
“…A low level of heterogeneity was present in the studies (I 2 = 0%, P = 0.70). In addition, Stein and Ellis, 13 Kasem and Sabry 16 and Rajavi et al 18 all reported both procedures demonstrated comparable levels of reduction compared to the pre-operative grade. On the other hand, Min et al 14 concluded that the sum of all the apparent inferior oblique muscle dysfunction for the eyes with anterior transposition averaged + 0.1 residual overaction per eye compared with an average of + 1.2 residual overuaction for eyes after myectomy (P = 0.001).…”
Section: Primary Outcome Residual Inferior Oblique Functionmentioning
confidence: 94%
See 1 more Smart Citation
“…Various surgical techniques have been reported to weaken the inferior oblique muscle to treat inferior oblique overaction. These include tenotomy (5, 6), 10-mm or 14-mm recession (7), myectomy (3, 8), anteriorization (anterior transposition) (3, 8, 9), extirpation and denervation (3, 10), graded recession-anteriorization (3, 11), anterior and nasal transposition (12), nasal myectomy (13), orbital wall fixation (14), hang-back recession (15), and Z-myotomy (16) of the inferior oblique muscle.…”
Section: Introductionmentioning
confidence: 99%